Comparison of the influence of aerobic and resistance exercise of the upper and lower limb on intraocular pressure. (7th January 2013) - Rüfer, Florian; Schiller, Johanna; Klettner, Alexa; Lanzl, Ines; Roider, Johann; Weisser, Burkhard
Abstract. Purpose: To compare the influence of aerobic and resistance exercise on intraocular pressure (IOP). Methods: Twenty‐one healthy subjects participated. Aerobic exercise was performed using a cycle ergometer, and resistance exercise was performed with a leg curl and a butterfly machine. Intraocular pressure was measured at baseline, during exercise and 10 min after. During resistance exercise, a Valsalva manoeuvre was prevented. Results: Before aerobic exercise, the mean IOP was 18.8 ± 2.7 mmHg. It was 16.5 ± 2.8 after 10, 17.1 ± 2.6 after 20 and 16.7 ± 3.3 mmHg after 30 min of exercise. After 10 min, the IOP returned to baseline (18.8 ± 2.7 mmHg). The mean IOP before resistance exercise with the leg curl machine was 17.0 (15.6–18.4; 65%Wmax) and 16.8 (15.3–18.3) mmHg; 75%Wmax) and did not change significantly during the experiment. The mean IOP before resistance exercise with the butterfly machine (65%Wmax) was 16.4 (15.2–17.6) and increased to 17.2 (16.0–18.4) mmHg (p < 0.05). After 10 min of recreation, it recovered to 16.3 (15.0–17.5) mmHg. At 75%Wmax, the mean baseline IOP was 16.3 (15.2–17.4) mmHg, and there were no significant changes. Conclusions: Aerobic exercise leads to a significant decrease of IOP. There was no influence of resistance exercise on IOP as long as a Valsalva manoeuvre was prevented.